Optimal placement and sizing of distributed generation unit by loading margin approach for voltage stability enhancement - Mamat, Nasirah (2015)
In the recent times, as the concern of continues and huge energy demand worldwide anticipated for future will be unrealistic if only governed by the central generation to transfer the huge power over the long distance. Parallel reason due to the increasing of interest on the alternative energy such as solar, wind, hydro, biomass, geothermal, tidal, wave and etc., the number of studies on integration of distributed resources to the grid has rapidly increased. Distributed Generation (DG) was known as generation which comprise of distributed resources and also local supply that close to the consumer or distribution network has the capability on aforementioned scenario. Further with the fluctuate costs of fuel and rigorous environmental regulations are the reasons for the construction of large power stations to meet rising energy demands economically unattainable. The penetration of DG presents a new set of conditions to distribution networks. One of the advantages of it is the ability to provide voltage support for better system stability. In other word it is like the reactive compensation system. However during DG installation, it may encounter other technical problem. One of the problems is improper placement of DG may actually increase the network losses and impact the voltage profile of the system. The DG problem can be solved by applying Loading Margin and Analytical approaches based on Newton-Raphson power flow to optimize the placement and size of DG and to enhance the voltage stability margin of power system to mitigate the risk of voltage collapse. There are three test system from IEEE 6-bus, IEEE 14- bus and IEEE 30-bus for the verification on the effectiveness of the methods applied. This project report concludes with appropriately locate and size of DG is the great options for voltage stability enhancement and system reactive power compensation.